The interaction of students' perceptions of classroom learning environment and their academic achievement / Azani Saleh, Lili Syahani Rusli and Roslinda Rosli - Saleh, Azani; Rusli, Lili Syahani; Rosli, Roslinda (Institute of Research, Development and Commercialization (IRDC), 2005)
An investigation of the relationships between the students' perceptions of classroom learning environment and their achievement in Biology at the matriculation level is described Classroom learning environment in Biology classes was measured using a questionnaire on "What Is Happening In This Class?" (WIHIC) which consistedofseven dimensions adaptedfrom Fraser et al. (/996). The questionnaires were administered to Year 12 (AUSMAT 17) and Year 11 (AUSMAT 18) Australian Matriculation Science students at the International Education Centre (INTEC) by the Biology teachers during regular class time. The data collected were analysed using descriptive statistics and Mann-Whitney Test. The results showed that both AUSMAT 17 and AUSMAT 18 students possessed high levels oftask orientation, cooperation but low levels ofinvolvement and investigation. Thefemale students perceived their learning environment more favourably than the male. The AUSMAT 12 students' achievement in Biology was significantly related to two dimensions in the WIHIC namely student cohesiveness and equity. Meanwhile. the AUSMAT 18 students showed significant relationships of the achievement in Biology between teacher support and task orientation. The findings of the present study have important implications to the Biology teachers at the matriculation level especially in INTEC to encourage their students to do more investigation and involvement in class discussions besides having good cooperation and task orientation in order to achieve better results in Biology.